2022
DOI: 10.3390/jcm11040985
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Soluble C-Type Lectin-like Receptor 2 Is Associated with the Worsening of Coronavirus Disease 2019

Abstract: Although thrombosis in coronavirus disease 2019 (COVID-19) infection has attracted attention, the mechanism underlying its development remains unclear. The relationship between platelet activation and the severity of COVID-19 infection was compared with that involving other infections. Plasma soluble C-type lectin-like receptor 2 (sCLEC-2) levels were measured in 46 patients with COVID-19 infection and in 127 patients with other infections. The plasma sCLEC-2 levels in patients with COVID-19 infection {median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…1, at the time of massive bleeding, was intubated, and sedation and mechanical ventilation were initiated. Wada et al [ 14 ], as a result of the conducted research, stated that platelet activation may be important in the worsening progress of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…1, at the time of massive bleeding, was intubated, and sedation and mechanical ventilation were initiated. Wada et al [ 14 ], as a result of the conducted research, stated that platelet activation may be important in the worsening progress of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…50 The elevated plasma levels of soluble CLEC-2 have been reported in patients with thrombotic microangiopathy and DIC, 51 52 as well as in patients with arterial thrombosis such as acute coronary syndrome 53 and acute cerebral infarction. 54 Wada et al 55 reported that the plasma levels of CLEC-2 in COVID-19 patients were significantly higher than in those with bacterial infections, and the levels reflected the severity of illness. Notably, the platelet counts were maintained within the normal range in those patients.…”
Section: Platelet-related Biomarkersmentioning
confidence: 99%
“…A second approach, used by Wada and collaborators, 8 is based on surrogate markers, that is, on the detection in plasma of molecules that could be released from activated platelets, with the idea that the higher the concentration of molecules released from platelets, the greater the extent of platelet activation. In their study, Wada and collaborators make a case for the role of C‐type lectin‐like receptor 2 (CLEC‐2).…”
Section: Figurementioning
confidence: 99%